Laminated film, sensor and tape

The laminated film with a specific alternating layer structure and thermal treatment process addresses the issue of decreased responsiveness in conventional smart polymer materials, achieving high and sustained shape fixation and restoration capabilities.

JP2025042705APending Publication Date: 2025-03-28TORAY INDUSTRIES INC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2023149794
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-15
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Conventional smart polymer materials used in laminated films, sensors, and tapes suffer from decreased responsiveness due to repeated deformation and restoration, leading to molecular structure damage and permanent set issues, which hinder their ability to maintain shape fixation and restoration functions.

Method used

A laminated film structure comprising 9 or more layers of alternating thermoplastic resin A and B, where the layer with the highest melting point (Tm) is designated as Layer A and the layer with the highest glass transition temperature or melting point (Tn) is designated as Layer B, is developed. This film undergoes a 50% stretch molding-reheating cycle test at Tn+20°C, achieving a dimension fixing rate of 90% or more and a dimension restoration rate of 80% or more after five cycles.

Benefits of technology

The laminated film exhibits high responsiveness to thermal stimuli, maintaining its shape fixation and restoration capabilities over multiple deformation and restoration cycles, ensuring long-term usability in applications such as sensors and tapes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025042705000001_ABST
    Figure 2025042705000001_ABST
Patent Text Reader

Abstract

To provide a flexible film which can be used with repeated deformation / restoration over a long period of time.SOLUTION: There is provided a laminated film having a structure formed by alternately laminating nine or more layers of an A layer composed of a polymer mainly comprising a thermoplastic resin A as a main component and a B layer composed of a polymer mainly comprising a thermoplastic resin B different from the thermoplastic resin A as a main component, wherein in accordance with JIS-K-7122 (1987), when the highest temperature of the glass transition temperature or melting point which appears in the region lower than the highest melting point Tm obtained from differential scanning calorimetry when approximately 5 mg of a sample is measured at a temperature rising rate of 20°C / minute is defined as Tn, the dimensional fixation rate after stretching is 80% or more when a 50% stretch molding-reheating cycle test is conducted at Tn+20°C and the dimensional restoration rate after reheating to the pre-test dimension is 80% or more.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention provides a laminated film, sensor, and tape that exhibit high responsiveness to thermal stimuli at or above a specific temperature, and that can be used over a long period of time while repeatedly deforming and recovering. [Background technology]

[0002] Smart polymers that can change the shape of materials by changing their molecular structure microscopically / macroscopically in response to external stimuli (heat, light, electricity, pH, magnetic field, etc.) have been actively researched and developed. Smart polymers are known to be composed mainly of a polymer component that exhibits elastic shrinkage behavior and a polymer component with high rigidity, and are made of a resin in which the two are kneaded, dispersed, or distributed. After being molded into a desired shape such as a sheet, tube, or string, they are being put to practical use in various applications by utilizing their function of deforming in response to a stimulus and then restoring their shape when stimulated again. For example, in medical applications, they are used in medical catheters by utilizing the change in elastic modulus of the polymer due to a stimulus, and in casts and dressing material base materials by utilizing their shape fixity. In industrial applications, they are used in process heat shrinkable films and fastening parts by utilizing the shape restoring force due to heat shrinkage, and in temperature sensors by utilizing the volume expansion and temperature dependency of the refractive index. In particular, smart polymer materials that utilize thermal stimuli have attracted attention as being the simplest and most practical of stimuli (Patent Documents 1 and 2).

[0003] In addition, most of the usual thermoresponsive smart polymer materials are fixed in shape and do not deform at room temperature; they deform at a certain high temperature, solidify when cooled, and return to their original shape when a thermal stimulus is applied to release the elastic contraction behavior. However, in recent years, the development of sheet materials that deform at human skin temperature, always exhibit drapeability when in contact with the skin, and can freely deform to fit the shape of the body has been reported (Patent Documents 3 and 4). In recent years, the demand for wearable devices has increased due to the growing interest in health care, and materials that can soften and deform at near body temperature are being used as wearless materials and tape base materials for various medical and sanitary materials in the hope of eliminating the drawback of wearable devices, which is the feeling of wearing them. In addition, in the past, technologies for personal care products such as diapers, medical applications, and clothing applications have been considered by combining a multilayer laminate structure and an elastically stretchable olefin resin as an elastic film material mainly intended for shape recovery (Patent Documents 5 and 6).

[0004] Such stimuli-responsive smart materials, which can respond and deform only under the necessary conditions, are expected to be put to practical use in a wide range of industrial and consumer applications in the future. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Japanese Patent Application Publication No. 4-122712 [Patent Document 2] Japanese Patent Application Publication No. 9-309986 [Patent Document 3] Patent Publication No. 2021-023499 [Patent Document 4] JP 2017-133011 A [Patent Document 5] Patent No. 04991742 [Patent Document 6] Japanese Patent Application Publication No. 5-501386 Summary of the Invention [Problem to be solved by the invention]

[0006] However, repeated deformation and restoration can destroy the molecular network and change the higher-order structure, gradually reducing the polymer's responsiveness to stimuli with continuous use, resulting in a decrease in both the amount of shape fixation and the amount of shape recovery.

[0007] In addition, conventional materials with multi-layer laminated structures that are primarily intended for shape recovery utilize the fact that, by performing a plastic deformation of at least 50% as a preliminary stretch, the shape does not return to a certain dimension depending on the amount of deformation, and permanent deformation remains, and there was no idea of ​​restoring the original shape. Furthermore, they lack the ability to maintain the state after plastic deformation, and when the stress is released after deformation, they automatically recover to a shape equivalent to the permanent deformation like rubber materials, so they were unable to demonstrate the shape fixation and shape recovery functions that are the main functions of smart materials.

[0008] Therefore, an object of the present invention is to provide a laminated film that can be used over a long period of time while repeatedly deforming and restoring, and a sensor and tape using the same. [Means for solving the problem]

[0009] That is, a preferred embodiment of the present invention is as follows. (1) A laminated film having a structure in which 9 or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from thermoplastic resin A are alternately laminated, and when Tn is the highest temperature among the glass transition temperatures or melting points appearing in a region lower than the highest melting point Tm obtained by differential scanning calorimetry measurement using a 5 mg sample at a heating rate of 20°C / min in accordance with JIS-K-7122 (1987), the laminated film has a dimensional fixation rate after stretching of 80% or more and a dimensional recovery rate after reheating of 80% or more relative to the dimensions before the test when subjected to a 50% stretch molding-reheating cycle test at Tn+20°C. Note that, a layer showing a melting point within ±5°C of the highest melting point Tm shown by the laminated film is defined as layer A, and a layer showing a temperature, which is the higher one between the glass transition temperature and the melting point of the layer, within ±5°C of Tn shown by the laminated film is defined as layer B. (2) The laminated film according to (1), wherein when the 50% stretching and reheating cycle test at Tn + 20°C is repeated 5 times, the dimensional fixation rate after stretching during the fifth test is 90% or more, and the dimensional restoration rate after reheating during the fifth test with respect to the initial dimension before the cycle test is 80% or more. (3) The laminated film according to (1) or (2), wherein the thermoplastic resin A is crystalline. (4) The laminated film according to any one of (1) to (3), wherein the thermoplastic resin B is amorphous and the glass transition temperature of layer B is Tn. (5) The laminated film according to any one of (1) to (4), wherein in the strain-stress curve in the tensile test at Tn + 20°C, the inflection point first appears when the strain is 50% or more upon performing differential analysis. (6) The laminated film according to any one of (1) to (5), wherein when the storage elastic modulus of layer A at temperature T (°C) is GA(T) (GPa) and the storage elastic modulus of layer B is GB(T) (GPa), 1.2GA(Tn - 10) < GB(Tn - 10) and GA(Tn + 10) ≥ 1.2GB(Tn + 10) are satisfied. (7) The laminated film according to any one of (1) to (6), wherein Tm and Tn satisfy Tm - Tn ≥ 30°C. (8) The laminated film according to any one of (1) to (7), wherein when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz in the temperature range from -80°C to the melting point Tm, two or more loss tangent peaks exist, and the relationship between the loss tangent peak tanδ1 occurring at the lowest temperature (temperature T1 (°C)) and the loss tangent peak tanδ2 occurring at the highest temperature (temperature T2 (°C)) is tanδ2 / tanδ1 ≥ 1.0. (9) The laminated film according to any one of (1) to (8), wherein the main component of the thermoplastic resin A consists of any one of polystyrene, polyester, polyurethane, and polyamide. (10) A sensor comprising the laminate film according to any one of (1) to (9) and a stretchable conductive layer laminated thereon. (11) The sensor according to (10), which is used by changing its shape or function within a temperature range of 20 to 100°C. (12) A tape comprising an acrylic or silicone adhesive layer provided on at least one surface of the laminate film according to any one of (1) to (9). (13) Water vapor permeability is 300(g 25μm / (m 2 The tape according to (12), which is used in a temperature range of 20 to 50°C while changing its shape or function, is used for a period of at least 1.5 days. Effect of the Invention

[0010] Even when deformation / recovery in response to stimuli is performed multiple times, the mechanical response is particularly in the direction along the laminate interface, so there is little change in the molecular structure network state of the entire polymer material before and after deformation, making it possible to use it as a flexible film substrate that can be used over a long period of time, while continuing to deform / recover. [Brief description of the drawings]

[0011] [Figure 1] FIG. 2 is a schematic diagram showing an example of the relationship between the depth in the thickness direction and the contrast difference (gray level) in a cross-sectional observation image of a laminate film having an (AB)x alternating laminate arrangement. [Diagram 2] FIG. 1 is a schematic diagram showing a differential calorimetric spectrum of an example of a laminate film using a crystalline thermoplastic elastomer and an amorphous thermoplastic resin having a glass transition temperature at a temperature Tn. [Diagram 3] FIG. 2 is a schematic diagram showing a differential calorimetric spectrum of an example of a laminate film using a crystalline thermoplastic elastomer and a crystalline thermoplastic resin that exhibits a glass transition temperature at a temperature Tn. [Figure 4] FIG. 2 is a schematic diagram of an example of a strain-stress curve when stretched at a temperature below Tn. [Diagram 5] FIG. 2 is a schematic diagram of an example of a strain-stress curve when stretched at a temperature of Tn+20° C. [Figure 6]FIG. 2 is a schematic diagram showing an example of a loss tangent spectrum in dynamic viscoelasticity measurement of a laminated film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The laminated film of the present invention will be described in detail below. A preferred embodiment of the laminated film of the present invention is a laminated film having a structure in which 9 or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from the thermoplastic resin A are alternately laminated, and the laminated film is characterized in that, when a 50% stretch molding-reheating cycle test is performed at Tn+20°C, where Tn is the highest temperature among the glass transition temperatures or melting points appearing in a region lower than the highest melting point Tm obtained by differential scanning calorimeter measurement when measuring about 5 mg of a sample at a heating rate of 20°C / min according to JIS-K-7122 (1987), the dimensional fixation rate after stretching is 80% or more and the dimensional recovery rate after reheating to the dimensions before the test is 80% or more.

[0013] In order to obtain a higher mechanical response to external thermal stimuli than that obtained by conventional single-layer film techniques using kneaded and dispersed polymers, the laminate film of the present invention is preferably a laminate film having a structure in which nine or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from the thermoplastic resin A are alternately laminated.

[0014] Thermoplastic resins that are "different" refer to cases where any of the following applies: (1) the compositions are different; (2) the glass transition temperatures or melting points are different in differential scanning calorimetry (DSC); (3) the contrast of images after dyeing when cross-sectionally observed by transmission electron microscopy (TEM) is different; (4) the dielectric constants of each layer are different in EELS measurements described below; or (5) the elastic moduli are different.

[0015] "Different compositions" means that the following conditions for "same composition" are not met: "Same composition" means that the repeating units in the chemical structures of both thermoplastic resins are 95 mol% or more in common, or that 95 mass% of the components of the thermoplastic resins are in common.

[0016] For example, in the case of the former, polyethylene terephthalate has as its main constituent unit a constituent unit (ethylene terephthalate unit) in which an ethylene glycol unit and a terephthalic acid unit are bonded by an ester bond, but when the amount of copolymerization component exceeds 5 mol%, such as polyethylene terephthalate obtained by copolymerizing homopolyethylene terephthalate and isophthalic acid at 10 mol%, the two thermoplastic resins are considered to have different compositions when they have a common chemical structure of polyethylene terephthalate. In addition, in the case of the latter, when one is homopolyethylene terephthalate and the other is a resin containing 90 mass% homopolyethylene terephthalate and the remaining 10 mass% is another component, the two thermoplastic resins are also considered to have different compositions when they have the same main constituent but have 5 mass% different components. The repeating unit structure of the specific composition / chemical structure of each thermoplastic resin can be identified by determining the layer thickness of each thermoplastic resin layer according to the methods described below in the "Laminated Cross-Section Image Acquisition" and "Layer Thickness Analysis" measurement methods, and then cutting and extracting the thermoplastic resin layer, or by scraping the layer to expose it as the outermost layer, using infrared spectroscopy (FT-IR method or nano-IR method), a gas chromatograph / time-of-flight mass spectrometer (GC-MS), or a nuclear magnetic resonance device (NMR).

[0017] On the other hand, if it is difficult to identify the composition by the above method while extracting each thermoplastic resin layer, the thermoplastic resin layers constituting the laminated film are judged to be "different" by showing different melting points and / or glass transition temperatures in differential scanning calorimetry (DSC). In the present invention, showing different melting points and different glass transition temperatures means that the melting points and glass transition temperatures differ by 2.0°C or more in the differential calorimetry spectrum when each thermoplastic resin layer is heated to a temperature above its melting point, then quenched and heated again. In addition, if the thermoplastic resin does not show a glass transition temperature or melting point in the measurement temperature range of -80°C to 280°C described in the section on differential scanning calorimetry (DSC) in the measurement method described later, if the thermoplastic resin constituting one layer shows a glass transition temperature or melting point and the thermoplastic resin constituting the other layer does not show a glass transition temperature or melting point, it cannot be calculated as a temperature difference, but the thermal properties of both resins may be interpreted as being different.

[0018] In addition, if it is difficult to identify by the above two methods, the layer interface due to the contrast difference can be confirmed in the cross-sectional image observed by transmission electron microscope observation, the brightness of each layer can be quantified, and if it can be confirmed that the difference in the average brightness of the two adjacent layers is greater than any of the standard deviations of the brightness of the adjacent thermoplastic resin layers, the adjacent thermoplastic resin layers are judged to be "different". If the composition of the thermoplastic resin constituting both thermoplastic resin layers is the same, it is considered that the thermoplastic resin layer formed using it will also show the same characteristics, so the sameness or difference of the thermoplastic resin can be judged from the state of the thermoplastic resin layer. Since this contrast occurs due to scattering of electron beams, crystal diffraction, etc., when the composition of the thermoplastic resin constituting the thermoplastic resin layer differs according to the above-mentioned criteria, the crystallinity and electron density state differ depending on the type and copolymerization amount of each thermoplastic resin, and the dyeing state differs, making it possible to visually recognize each layer as a layer structure with a contrast difference in the cross-sectional image of the laminate film.

[0019] In the case of a laminated film having two different types of thermoplastic resin layers, each thermoplastic resin layer shows a constant brightness, so if the depth in the thickness direction is plotted on the horizontal axis and the brightness and contrast (gray level in a grayscale display) at each point on the vertical axis, the graph will show repeated ups and downs between the brightness of two points, as shown in Figure 1. The symbols 1 to 3 in Figure 1 respectively represent the spectrum showing the relationship between the depth in the thickness direction and the change in contrast (gray level) of a laminated film having an (AB)n (n is a natural number) regular arrangement, the layer thickness of layer A, and the layer thickness of layer B, respectively.

[0020] If it is difficult to distinguish them by the contrast difference, the two thermoplastic resins are judged to be "different" from the dielectric constant of each thermoplastic resin layer obtained by electron energy loss spectroscopy (EELS measurement). As described above, the crystallinity and electron density state differ depending on the type and copolymerization amount of the thermoplastic resin, and the response (interaction) state of the molecules to the electromagnetic field changes, so that differences also appear in the electron scattering state, and a numerical difference in the dielectric constant depending on the material state appears. Specifically, an electron beam is irradiated to each thermoplastic resin layer in the cross-sectional sample, and the dielectric constant is analyzed to read the dielectric constant at a loss energy of 2.5 eV. If the difference in the dielectric constant of the obtained thermoplastic resin layers is 0.01 or more, the refractive index of the thermoplastic resin layers is judged to be "different".

[0021] Furthermore, if the thermoplastic resin layers cannot be determined to be "different" by the above four methods, when the cross-section of the laminated film is tapped while sweeping at a constant temperature according to "AFM tapping elastic modulus measurement" described in the measurement method section below, the two thermoplastic resin layers are determined to be "different" when the elastic modulus at corresponding positions of the different thermoplastic resin layers shows a numerical difference of 1% or more. In particular, since the laminated film of the present invention is characterized in that the elastic modulus of both thermoplastic resins changes depending on the glass transition temperature, the elastic modulus may be measured at multiple temperatures (three or more points) differing by 30°C or more, and if a difference in elastic modulus is detected at any one point, the two thermoplastic resins may be determined to be "different".

[0022] Representative thermoplastic resins that can be used to form layers A and B of the laminated film of the present invention are shown below, but the thermoplastic resins that can be used in the present invention are not limited to those shown below. For example, polyolefin resins such as polyethylene, polypropylene, poly(1-butene), poly(4-methylpentene), polyisobutylene, polyisoprene, polybutadiene, polyvinylcyclohexane, polystyrene, poly(α-methylstyrene), poly(p-methylstyrene), polynorbornene, and polycyclopentene; polyamide resins such as nylon 6, nylon 11, nylon 12, and nylon 66; copolymer resins of vinyl monomers such as ethylene / propylene copolymer, ethylene / vinylcyclohexane copolymer, ethylene / vinylcyclohexene copolymer, ethylene / alkyl acrylate copolymer, ethylene / acrylic methacrylate copolymer, ethylene / norbornene copolymer, ethylene / vinyl acetate copolymer, propylene / butadiene copolymer, isobutylene / isoprene copolymer, and vinyl chloride / vinyl acetate copolymer; polyacrylate, polyisobutyl methacrylate, and polymethacrylate; Examples of the polymer that can be used include acrylic resins such as polymethyl methacrylate, polybutyl acrylate, polyacrylamide, and polyacrylonitrile; polyester resins such as polyethylene terephthalate, polypropylene terephthalate, polybutylene terephthalate, and polyethylene-2,6-naphthalate; biodegradable polymers such as polylactic acid and polybutyl succinate; and polyurethane, polyvinyl chloride, polyvinylidene chloride, polycaprolactone, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyacetal, polyglycolic acid, polycarbonate, polyketone, polyether sulfone, polyether ether ketone, modified polyphenylene ether, polystyrene, polyphenylene sulfide, polyetherimide, polyimide, polysiloxane, tetrafluoroethylene resin, trifluoroethylene resin, trichloroethylene resin, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinylidene fluoride.

[0023] The laminated film consisting of different thermoplastic resin layers will be described in detail below, but thermoplastic resins with completely different structures can also be combined, and different thermoplastic resins can be made by alloying, blending, or copolymerizing.

[0024] It is desirable for the laminated film of the present invention to exhibit a function of being able to convert and restore the shape of the laminated film in a temperature range exceeding a specific temperature, and in order to achieve this function, it is preferable that at least one of the thermoplastic resins constituting the laminated film is a thermoplastic elastomer (TPE) resin that softens and exhibits elastic stretch behavior (rubber elastic behavior) in that temperature range. Elastic stretch behavior (rubber elastic behavior) cannot be achieved only by a composition that contains an aromatic ring and forms a strong structure by π conjugation and intermolecular forces, and is often achieved by including a soft segment component consisting of a relatively long aliphatic chain structure having 4 or more carbon atoms in the molecular structure by copolymerization or the like. In addition, in order for such elastic stretch behavior to be put into practical use for consumer and industrial purposes, it is preferable that the thermoplastic elastomer exhibits elastic stretch behavior in the practical and processing temperature range of room temperature or higher and lower than 140°C, has a melting point in a temperature range higher than that, and exhibits heat resistance, flexibility, and high strength.

[0025] Examples of thermoplastic resins that can satisfy such characteristics include polyester-based TPEs (polyester resins containing polytetramethylene glycol copolymers, etc.), polyamide-based TPEs (polyether block amides, polyester amides, polyether ester amides, polycarbonate ester amides, etc.), thermoplastic polyurethane resins (aliphatic polyester urethane resins, aliphatic polyether urethane resins, etc.), polystyrene-based elastomers (styrene butadiene styrene resins, styrene isoprene styrene resins, styrene ethylene butylene styrene resins, ethylene ethylene propylene styrene resins, etc.), and polyolefin-based elastomers. In addition, resins obtained by dispersing / mixing these resins into alloys can also be used. In addition, resins that do not exhibit elastic stretching behavior as the main components constituting the thermoplastic resin layer may be designed to become polymers that exhibit elastic stretching behavior by kneading and dispersing these components as additives in the thermoplastic resin.

[0026] Furthermore, in order for the laminated film of the present invention to exhibit the shape change / restoration function, it is desirable that the second thermoplastic resin different from the thermoplastic elastomer resin softens to such an extent that it does not exhibit rigidity, with the above-mentioned specific temperature as the boundary. Specifically, as described later, it is preferable that the design is such that the magnitude of the elastic modulus of thermoplastic resin A and thermoplastic resin B is reversed with the specific temperature as the boundary. In addition, when the second thermoplastic resin softens, the thermoplastic resin may be in a rubber elastic state at the above temperature or higher, or may be melted and in a molten state, as long as it does not interfere with the expansion and contraction behavior of the TPE resin. The glass transition temperature or melting point of the second thermoplastic resin determines the shape change temperature of the laminated film as the above-mentioned specific temperature. In other words, in the temperature range in which the thermoplastic elastomer exhibits a rubber-like elasticity region, the second thermoplastic resin switches between solidification and softening, thereby realizing shape change and restoration. Therefore, since the thermal properties of the second thermoplastic resin are responsible for the shape change / restoration function, a thermoplastic resin may be appropriately selected according to the desired use and temperature range. Such a thermoplastic resin can be appropriately selected from the various thermoplastic resins listed above.

[0027] In addition, it is preferable that the thermoplastic elastomer resin exhibits crystallinity. The crystallinity mentioned here can be determined using a differential scanning calorimetry (DSC) analyzer. Specifically, in the spectrum obtained by extracting a layer containing the thermoplastic resin, heating it once to melt it, then quenching it, and heating it again, the crystalline thermoplastic resin is characterized by exhibiting three points: glass transition temperature, crystallization enthalpy which is an endothermic peak, and fusion enthalpy which is an exothermic peak. In particular, the fusion enthalpy is a characteristic that is not exhibited by amorphous resins. On the other hand, amorphous resins are characterized by not having fusion enthalpy and only exhibiting glass transition temperature. By making the elastomer resin crystalline, the processability, heat resistance, durability, chemical resistance, strength, etc. can be improved compared to amorphous resins, so this is preferable when considering the use of the laminated film of the present invention, which is used repeatedly. In addition, when extracting each layer, it is preferable to extract a layer at a location where there is no layer disorder and a layer structure is exhibited.

[0028] On the other hand, in order for the layers of two different types of thermoplastic resins constituting the laminated film to uniformly follow changes in shape and dynamically respond to the force that deforms the laminated film as a whole, it is preferable that the adjacent thermoplastic resins constituting each layer exhibit high compatibility to the extent that they exhibit non-peeling properties. Specifically, the compatibility between thermoplastic resins can be expressed as the difference in compatibility parameter (SP value). The compatibility parameter is a parameter related to the energy specific to the thermoplastic resin, and the closer these values ​​are to each other, the higher the affinity is, such as the similarity of the skeletal structure, and the higher the adhesion at the resin layer interface is. The compatibility parameter can be estimated by calculation methods such as Hansen, Hoy, and Fedors, but the compatibility parameter of thermoplastic resins, which are organic polymer materials, will be calculated using the Fedors calculation method, which can be calculated based on the molecular structure of the resin. By using this method, the compatibility parameter of a thermoplastic resin containing a structural unit derived from a copolymerization component can also be easily calculated in ratio according to the ratio of each structural unit. In the Fedors calculation method, the cohesive energy density and molar volume of a molecule, which depend on the type and number of substituents, determine the compatibility parameter, and the compatibility parameter is estimated according to formula (1). Here, E coh (cal / mol) is the cohesive energy and V is the molar volume (cm 3 / mol).

[0029]

number

[0030] The compatibility parameter of the laminated film of the present invention is a value obtained by rounding off the estimated value calculated based on Fedor's formula to one decimal place. This method is described in F. Fedors, Polym. Eng. Sci., 14(2), 147 (1974).

[0031] In order for adjacent thermoplastic resin layers to exhibit good non-peeling properties, it is preferable that the difference in compatibility parameters (SP values) between adjacent thermoplastic resin layers is 2.5 or less. More preferably, the difference in SP value is 2.0 or less, and even more preferably 1.5 or less. In order to reduce the difference in SP value, the molecular skeleton of the repeating unit constituting the thermoplastic resin should be similar between adjacent thermoplastic resins in terms of aliphatic / aromatic, the chain length of the aliphatic difference, the type of functional group component, etc.

[0032] The layers A and B in the laminated film of the present invention are composed of polymers mainly composed of thermoplastic resin A and thermoplastic resin B, respectively. The main component as described here means a component contained in the polymer constituting the layer at a ratio of more than 50% by mass to 100% by mass. In this case, the thermoplastic resin may be a copolymer resin, an alloyed blend resin, or a thermoplastic resin obtained by kneading, dispersing, mixing, and distributing two types of the same type of polymers that are the same resin components but have different compositions and properties such as polymerization degree and melt viscosity. Examples of minor components that are not the main components include minor components contained in the above-mentioned thermoplastic resins, such as inorganic components and functional low-molecular organic components other than thermoplastic resins. Specific examples of such minor components include light absorbers (ultraviolet absorbers, dyes, pigments, heat absorbers), antioxidants, light stabilizers, quenchers, heat stabilizers, weather stabilizers, organic lubricants, fillers, antistatic agents, nucleating agents, and flame retardants. These minor components can be freely added to each layer to the extent that the original physical properties and functions of the film are not impaired.

[0033] When an alloyed blend resin is used as the resin constituting layer A or layer B, the thermoplastic resin constituting each layer refers to the thermoplastic resin that is the main component of the blended raw materials. For example, when using a resin in which two types of resin a and resin b are alloyed so that the ratio of resin a is higher, resin a is defined as the thermoplastic resin described in this invention. When the two are blended in a ratio of exactly 50:50, both resin a and resin b are considered to be the main components.

[0034] Among these subcomponents, depending on the type of thermoplastic resin constituting each thermoplastic resin layer, there are cases where deterioration is accelerated by absorbing ultraviolet light with high energy intensity. Therefore, it is also preferable to include an ultraviolet absorber or an antioxidant for the purpose of suppressing photodegradation by causing a competitive reaction.

[0035] The laminated film of the present invention preferably has a structure in which 9 or more layers of A and B are alternately laminated. By using a film having such a laminated structure, a structure is formed in which polymer molecules are likely to respond in the in-plane direction of the film during the manufacturing process, and further, the laminated resin interface is aligned in the in-plane direction, so that a material with high shape recovery function and little residual tensile strain can be obtained. In addition, since a highly rigid resin that controls shape fixation and a resin that shows elastic stretchability exist independently, the shape fixation ability can be improved compared to a single-layer film material using a conventional kneaded and dispersed polymer.

[0036] In the present invention, alternate lamination refers to the fact that the thermoplastic resin A constituting the A layer and the thermoplastic resin B constituting the B layer are laminated in a regular arrangement in the thickness direction, and refers to a state in which the resins are laminated according to a regular arrangement of A(BA)n (n is a natural number), B(AB)n (n is a natural number), or (AB)n (n is a natural number). When producing a laminated film having the configuration of A(BA)n or B(AB)n, a plurality of resins, namely, thermoplastic resin A and thermoplastic resin B, are sent out from different flow paths using two or more extruders, and a multi-manifold type feed block or a square mixer, which is a known lamination device, can be used. In particular, in order to efficiently obtain the configuration of the present invention, a method using a feed block having fine slits is preferable because it realizes high-precision lamination and improves the shape fixing and shape restoration properties. In the case of the square mixer method, the number of layers can be easily doubled by dividing the molten laminate flowing in the polymer pipe in the middle and overlapping the halves of the molten laminate while stretching each half. However, the cross-sectional area of ​​the flow path through which the resin flows changes during the process from division to merging, which may cause the laminate state to collapse and cause lamination disorder. This may result in the shape fixation / restoration properties that should be obtained with the same number of layers not being obtained. When forming a laminate unit using a slit-type feed block, the thickness and distribution of each layer can be achieved by changing the length and width of the slit to gradient the pressure loss. The length of the slit is the length of the comb teeth that form the flow path for flowing layers A and B alternately in the slit plate. In the case of B(AB)n (n is a natural number), it is sufficient to interpret it by exchanging thermoplastic resin A and thermoplastic resin B. Therefore, in the following, the laminate film will be described as having a configuration of A(BA)n (n is a natural number).

[0037] Of the structures A(BA)n and (AB)n, the structure A(BA)n is more preferable. By forming both outermost layers from the same layer, the laminated film can be produced by the same production method as that for the monolayer film made of the thermoplastic resin.

[0038] Furthermore, as the arrangement of the thermoplastic resin for the structure in which the A layer and the B layer are alternately laminated, the A layer and the B layer are alternately arranged, and an intermediate layer (C layer) adjacent to both layers is arranged, such as an (ACBC)n structure or (ACB)nA structure, or a laminate structure such as C(AB)nC having an (AB)n regular arrangement and a different layer on the outermost layer can be used. In this case, it is preferable that the A layer and the B layer are alternately included in 9 layers. By including this regular arrangement, the thermoplastic resin constituting the C layer is selected to include a thermoplastic resin containing an intermediate element compatible with both the thermoplastic resin A constituting the A layer and the thermoplastic resin constituting the B layer, thereby increasing the interlayer adhesion of the laminate film, and making it possible to obtain a laminate film that can be used repeatedly for a long period of time.

[0039] In the laminated film of the present invention, the presence of multiple thermoplastic resins is determined by the definition of the "different" thermoplastic resin layers. As described below, A layer, B layer, C layer, etc. are defined according to the thermal properties of each layer, but considering that the thermal properties obtained from the entire laminated film and the thermal properties measured for each resin layer may differ due to measurement errors, the layer whose melting point is ±5°C of the highest melting point Tm of the laminated film is defined as A layer, the layer whose glass transition temperature or melting point, whichever is higher, is ±5°C of Tn of the laminated film is defined as B layer, and the other layers are defined as C layer, D layer, etc. in order of increasing glass transition temperature. In addition, according to the above definition, it is preferable that the melting point Tm and the shape conversion point Tn described below are Tm-Tn>5°C by definition.

[0040] In addition, although each layer is made of a polymer whose main component is a "different" thermoplastic resin, if the melting point of each layer is within ±5°C of the highest melting point Tm of the laminated film, the layer with the greater number of layers is called Layer A, and the layer with the fewer number of layers is called Layer C, Layer D, etc. The same applies to Layer B.

[0041] In addition, the laminated film of the present invention may be provided with a hard coat layer, an easy adhesion layer, a gas barrier layer, an adhesive layer, a peeling layer, etc., separately on at least one side as a functional layer on the outermost surface of the laminated structure showing the regular arrangement of A(BA)n. In particular, as described later, the laminated film of the present invention is preferably a thermoplastic elastomer resin that is crystalline and can exhibit elastic stretching behavior as the thermoplastic resin A constituting the A layer, which is the surface layer of the laminated film, but such a resin may be insufficiently cooled in the casting process, exhibit tackiness to a normal metal roll, and not peeled off, causing a problem of the laminated film wrapping around the roll. In order to improve the cast peelability, a method of eliminating tackiness may be considered, such as changing the roll material to one that matches the surface layer polymer, or coating the cast drum surface with a release agent or release treatment, but the effect may decrease over time, or the component may remain on the surface of the laminated film, affecting the physical properties of the laminated film. Therefore, a method of stabilizing the casting process by laminating a thermoplastic resin that does not exhibit tackiness to a metal roll and can be peeled off from the laminated film showing the elastic stretching behavior later on the outermost layer as a peeling layer by coextrusion can be suitably used. However, the judgment of the thermoplastic resins that are "alternately laminated" as described in the present invention is limited to the portions that show a regular arrangement.

[0042] In the laminated film of the present invention, the thermoplastic resin A mainly used in the A layer arranged in the outermost layer is preferably a crystalline resin. By using a crystalline resin, it is possible to obtain a good molded product without adhesion to clips, molds, or rolls during thermoforming (stretching) processing, and the laminated film becomes a material with excellent heat resistance, durability, strength, and moldability due to the effect of the crystalline resin arranged in the outermost layer, and can be handled in the same manner as a single-layer film material using a crystalline resin. Therefore, it is preferable that the outermost layers on both sides of the laminated film are crystalline resins, and further, in order to fully exert the shape fixation / restoration of the present invention, they are crystalline thermoplastic elastomer resins that exhibit rubber elastic behavior. In addition, since the basic shape to which the laminated film of the present invention is restored after reheating is a shape formed at a temperature near the melting point, the basic shape of the material to be transformed is given at a temperature equal to or higher than the melting point of the crystalline resin.

[0043] Among the thermoplastic elastomers described above, the thermoplastic resin A is preferably selected from any of polystyrene, polyester, polyurethane, and polyamide resins from the viewpoints of versatility, flex resistance, and strength. Furthermore, from the viewpoints of the resistance to deformation strain of the laminated film after deformation / restoration cycles and weather resistance, it is more preferable that the thermoplastic resin A is one selected from the group consisting of polyurethane, polyester, and polyamide resins. Furthermore, from the viewpoints of film formability by melt extrusion and heat resistance, it is preferable that the thermoplastic resin A is polyester or polyamide. By selecting these resins, the range of types of thermoplastic resins that can be selected according to the desired shape transformation temperature is expanded, and the applicable temperature range as a shape fixing / restoring material can be expanded. On the other hand, in the case of tape applications described later, the tape is used in close contact with the human body for a long time, so water vapor permeability that does not interfere with skin breathing may be required. When used for such applications, it is preferable to select from polyurethane resins, polyamide resins, and the like.

[0044] The laminated film of the present invention preferably includes a structure in which an A layer mainly made of a thermoplastic resin A and a B layer mainly made of a thermoplastic resin B different from the thermoplastic resin A are alternately laminated in 9 or more layers. By increasing the number of layers contained in the laminated film, the layer made of the thermoplastic resin softened at a certain temperature or higher is more likely to follow the deformation of the adjacent thermoplastic elastomer resin exhibiting crystalline elastic behavior and to respond mechanically. If the number of layers is less than 9, the thickness of each layer constituting the laminated film is large, so that the softened thermoplastic resin layer does not sufficiently deform and respond mechanically to follow the behavior of the adjacent thermoplastic elastomer resin, and the response of shape deformation / restoration may be reduced. More preferably, the number of layers is 51 layers or more, even more preferably, 101 layers or more, and particularly preferably, 301 layers or more. Although there is no upper limit to the number of layers, as the number of layers increases, problems such as an increase in manufacturing costs due to the increase in the size of the manufacturing equipment and a tendency for lamination disorder to occur due to the non-Newtonian viscosity behavior of the elastic elastomer resin arise, so that in reality, the practical range is 1000 layers or less.

[0045] In the laminated film of the present invention, when Tn is the highest glass transition temperature or melting point appearing in a region lower than the highest melting point Tm obtained in a differential scanning calorimeter (DSC) measurement using a 5 mg sample at a heating rate of 20°C / min according to JIS-K-7122 (1987), and a 50% stretch molding-reheating cycle test is performed at Tn+20°C, it is preferable that the dimensional fixity after stretching is 80% or more and the dimensional recovery rate after reheating to the dimensions before the test is 80% or more.

[0046] The thermal properties obtained when the laminate film of the present invention is analyzed by differential scanning calorimetry will be described with reference to FIGS.

[0047] Figure 2 shows a schematic diagram of a differential calorimeter spectrum of a laminated film using a crystalline thermoplastic elastomer as one thermoplastic resin and an amorphous thermoplastic resin showing a glass transition temperature at temperature Tn as the other thermoplastic resin. Here, the endothermic peak indicated by reference number 7 indicates the melting point Tm derived from the crystalline thermoplastic elastomer, the step region indicated by reference number 6 indicates Tn appearing in a region lower than the melting point Tm, and reference number 5 indicates the glass transition temperature derived from the crystalline thermoplastic elastomer appearing in an even lower temperature region. Here, the crystalline thermoplastic elastomer can exhibit stretching behavior as a rubber-like region in the temperature range indicated by reference number 8 from the glass transition temperature of the resin to the melting point Tm.

[0048] Here, it is preferable that the glass transition temperature of the amorphous thermoplastic resin coincides with the above Tn. If the glass transition temperature of the amorphous thermoplastic resin is the lowest glass transition temperature indicated by reference symbol 5, the thermoplastic resin B is always substantially in a molten state in the temperature range above that, and in addition to being unable to fully retain the deformation caused by the thermoplastic elastomer, there may be a problem that the deformation during molding becomes non-uniform. For this reason, it is preferable to design the amorphous thermoplastic resin to have a temperature Tn, and to switch between solidification and melting around the temperature Tn, thereby allowing control of shape deformation, fixation, and restoration.

[0049] In light of the above, it is preferable that the laminated film of the present invention is designed such that the glass transition temperature of the thermoplastic resin A exhibiting elastic stretch behavior, the glass transition temperature of the amorphous thermoplastic resin B, and the melting point of the thermoplastic resin A are arranged in this order. At this time, the temperature range exceeding the glass transition temperature of the thermoplastic resin A and lower than the glass transition temperature of the thermoplastic resin B is the temperature region in which the shape of the laminated film is fixed by the rigidity exhibited by the thermoplastic resin B, and the temperature range is preferably 30°C or more and less than 200°C. Furthermore, the temperature range exceeding the glass transition temperature of the thermoplastic resin B and lower than the glass transition temperature of the thermoplastic resin A is the region in which the laminated film can exhibit shape deformation and shape recovery characteristics, and the temperature range is preferably 30°C or more and 250°C or less. These temperatures can be appropriately set according to the functions required for the laminated film of the present invention.

[0050] FIG. 3 shows a schematic diagram of the differential calorimetric spectrum of a laminated film using a crystalline thermoplastic elastomer as one thermoplastic resin and a highly rigid crystalline thermoplastic resin as the other thermoplastic resin. In this case, reference numeral 7 indicates the melting point of the highly rigid crystalline thermoplastic resin, and the elasticity of the thermoplastic elastomer can be expressed or stopped by switching between the rubber-like region and the molten state. Two points, reference numerals 5 and 9, may be obtained as glass transition temperatures that appear in a lower temperature region, and this should be set appropriately depending on the type of thermoplastic resin. However, thermoplastic elastomer A is a resin that shows the glass transition temperature (corresponding to reference numeral 5) at the lowest temperature, and the resin composition is functionally separated between an elastic resin and a highly rigid resin, which is suitable for enhancing the shape fixation / restoration properties and temperature responsiveness of the present invention.

[0051] In the case of the above laminated film configuration, it is preferable to design the laminated film so that the glass transition temperature of the thermoplastic resin A exhibiting elastic stretch behavior, the melting point of the highly rigid crystalline thermoplastic resin B, and the melting point of the thermoplastic resin A are arranged in this order. At this time, the temperature range exceeding the glass transition temperature of the thermoplastic resin A and lower than the melting point of the thermoplastic resin B is the temperature region in which the shape of the laminated film is fixed by the rigidity exhibited by the thermoplastic resin B, and the temperature range is preferably 30°C or more and less than 200°C. Furthermore, the temperature range exceeding the melting point of the thermoplastic resin B and lower than the melting point of the thermoplastic resin A is the region in which the laminated film can exhibit shape deformation and shape recovery characteristics, and the temperature range is preferably 30°C or more and 250°C or less. These temperatures can be appropriately set according to the functions required for the laminated film of the present invention.

[0052] The thermoplastic resin (thermoplastic resin B) different from the thermoplastic elastomer is preferably an amorphous thermoplastic resin as shown in the former. As a result, in the case of using a crystalline thermoplastic resin as in the latter, the resin is not completely solidified at a temperature lower than the melting point of the resin, and exhibits elastic stretch behavior in a temperature range up to the glass transition temperature. In this case, the thermoplastic resin B cannot completely control the ON / OFF stretch behavior of the thermoplastic elastomer, and the dimensional fixation rate may be reduced. Therefore, it is preferable that the thermoplastic resin B is an amorphous thermoplastic resin that can cause a large change in elastic modulus due to solidification / melting of the thermoplastic resin B and bring about a large change in elastic modulus relative to the elastic modulus of the thermoplastic elastomer. From the above, it is particularly preferable that the thermoplastic resin B is an amorphous thermoplastic resin that exhibits a glass transition temperature Tn.

[0053] The laminated film of the present invention is subjected to a 50% stretching-reheating cycle test at Tn+20°C to quantitatively evaluate the dimensional fixation before and after stretching and the dimensional recovery after reheating. The stretching-reheating cycle test, which will be described in detail in the section on measurement methods below, refers to a series of steps in which a sample of a certain length is uniaxially stretched to 1.5 times (50% strain) at Tn+20°C using a sheet stretcher KARO-V manufactured by Bruckner, cooled and solidified until the film temperature is displayed as a film temperature below Tn, and the obtained stretched sample is left to stand (reheated) for 1 minute under no load in a hot air oven at Tn+20°C. Here, when the sample length before the test is d, the sample length after uniaxial stretching + cooling and solidification is d1, and the sample length after reheating in the oven is d2, the dimensional fixation rate after stretching is expressed by formula (2), and the dimensional recovery rate after reheating to the size before the test is expressed by formula (3).

[0054]

number

[0055]

number

[0056] The dimensional fixation rate in the 50% stretch molding-reheat cycle test (first time) obtained by the above method is preferably 80% or more, and the dimensional recovery rate is preferably 80% or more. The dimensional fixation rate quantifies the ability to maintain the desired shape without shrinking and recovering after stretching and forming into the desired shape, and a large value indicates the property that the material can be used while maintaining the desired shape. If the dimensional fixation rate is below 80%, the material's shape fixation ability is insufficient, and for example, in the case of medical plaster, fixation is weak, leading to a decrease in healing power, and in the case of sensor use, the desired change amount is not obtained, leading to a problem that the sensor function cannot be obtained. Therefore, it is preferable that the dimensional fixation rate is high, more preferably 90% or more, and even more preferably 98% or more. Needless to say, 100% is optimal. In order to achieve a dimensional fixation rate of 80% or more, it is necessary to design thermoplastic resin B having a softening point or melting point at temperature Tn to be made of an amorphous resin, to design the elastic modulus of layer B, which is mainly composed of thermoplastic resin B, which is preferably used as an amorphous resin, to be 1.2 times or more higher than the elastic modulus of layer A, which is mainly composed of thermoplastic resin A, which is preferably used as a thermoplastic resin elastomer at temperatures lower than temperature Tn, and to increase the number of layers.

[0057] On the other hand, the dimensional recovery rate is a value that quantitatively indicates how much a material that has been shaped into a desired shape will return to its original shape when it is heated again, and a large value indicates that the material can be used repeatedly with the same properties by returning to its original state. If the dimensional recovery rate is below 80%, the material's shape recovery ability is insufficient, so for example, in the case of a medical cast, when you want to change the shape and fixation state of the cast depending on the healing situation, the shape does not follow the body sufficiently, which reduces the healing ability, or in sensor applications, the desired change cannot be obtained, which can lead to problems in which the sensor function cannot be obtained. Therefore, it is preferable that the dimensional recovery rate is high, more preferably 90% or more, and even more preferably 95% or more. Regarding the dimensional recovery rate, there are some materials that are difficult to restore 100% of their shape because the molecular structure causes permanent distortion in the material due to stretching. The closer to 100% recovery, the better the shape recovery ability. In order to achieve a dimensional recovery rate of 80% or more, at temperatures exceeding temperature Tn, it is necessary to design the elastic modulus of layer A, which is mainly composed of thermoplastic resin A and which is preferably a thermoplastic resin elastomer, to be 1.2 times or more higher than the elastic modulus of layer B, which is mainly composed of thermoplastic resin B and which is preferably an amorphous resin, to increase the number of layers, and to set the temperature difference between temperature Tn and melting point Tm to be 30°C or more.

[0058] As an index showing that the shape fixing / restoring properties of the laminated film of the present invention are superior to those of the conventional single-layer film technology using a kneaded dispersion polymer, when the 50% stretch molding-reheating cycle test at Tn+20°C is repeated five times, the dimensional fixation rate after stretching in the fifth test is preferably 90% or more, and the dimensional restoration rate after reheating in the fifth test is preferably 80% or more relative to the initial dimensions before the cycle test. Regarding the dimensional fixation rate, the polymer molecular structure transformation accompanying stretching becomes less likely to occur each time the stretching process is repeated, and the molecular structure shown for each shape change is stable for the same amount of shape change, so the value tends to increase as the number of cycle tests is repeated. Among them, a dimensional fixation rate of more than 90% is preferable as a suitable shape fixing material to be used repeatedly, even when the permanent deformation of the material is taken into consideration, and the material's sufficiently high shape fixing ability leads to, for example, in the case of a medical cast, the fixation is strong, improving the healing ability, and in the case of a sensor application, the desired amount of change is obtained, leading to improved function as a sensor. More preferably, it is 95% or more, and even more preferably 99%. Since molecular structure transformation during repeated testing is likely to occur due to crystalline components in the molecular structure, this can be achieved by having a low amount of crystalline components in the laminate film as a whole. In other words, the lamination ratio of thermoplastic resin B, which contributes to dimensional fixation, is large (the ratio of the total thickness of layer A, whose main component is thermoplastic resin A, to the total thickness of layer B, whose main component is thermoplastic resin B, is small), and an amorphous resin is used as thermoplastic resin B.

[0059] Furthermore, the dimensional recovery rate tends to increase and deteriorate with each cycle of shape deformation, compared to the initial dimension before the test, due to the occurrence of the molecular structure conversion. Therefore, a high dimensional recovery rate indicates the repetitive properties of the shape fixing / restoring material, and therefore a high numerical value is preferable. Here, the dimension after the fifth test is measured based on the dimension before the first cycle test, and the dimensional recovery rate after the fifth test is calculated. The dimensional recovery rate after the fifth cycle test is more preferably 90% or more, and even more preferably 95% or more. In order to increase the shape recovery rate even in repeated tests, it is preferable to select a resin that is unlikely to form a crystal structure and has small permanent distortion as the thermoplastic elastomer resin. Specifically, it is preferable to select from polystyrene-based elastomer resins, polyester-based elastomer resins, amide-based elastomer resins, etc., as the lamination ratio of two types of thermoplastic resins, a high ratio of thermoplastic resin A that shows elastic stretch behavior that is likely to leave permanent distortion after processing, and a high ratio of thermoplastic resin B that has high rigidity are both causes of a decrease in dimensional recovery, so it is easy to achieve this by indicating a lamination ratio range of 0.3 to 3.0. More preferably, it is in the range of 0.3 or more and 1.5 or less, and even more preferably, it is in the range of 0.3 or more and 1.0 or less.

[0060] The laminated film of the present invention preferably has a lamination ratio of 0.3 or more and 1.5 or less. In accordance with the preferred design in which the thermoplastic elastomer is arranged in the outermost layer, the lamination ratio is defined as the ratio of the thickness of the A layer including the outermost layer to the B layer made of a highly rigid thermoplastic resin. When the lamination ratio exceeds 1.5, the influence of the elastic behavior of the thermoplastic elastomer may be high even in the case of a laminated film, and when the lamination ratio is below 0.3, the influence of the highly rigid B layer may become dominant, resulting in a decrease in the shape recovery force. In order to combine the shape fixation / recovery ability of the laminated film at a specific temperature with the strength of the laminated film at room temperature, it is preferable that the ratio of the highly rigid thermoplastic resin constituting the laminated film is relatively high, and the lamination ratio is more preferably 0.3 or more and 1.0 or less. The lamination ratio can be adjusted by the discharge ratio of the extruder that supplies different thermoplastic resins. At this time, the discharge ratio and the thickness ratio may be affected by the polymer density and therefore may have different numerical values ​​in the strict sense, and should be appropriately adjusted taking into account the resin density according to the type of thermoplastic resin.

[0061] In the laminated film of the present invention, it is preferable that the inflection point in differential analysis appears for the first time in a region of 50% or more strain in the strain-stress curve in a tensile test at Tn+20° C. Regarding the strain-stress curve, a schematic diagram of the strain-stress curve when stretched at a temperature below Tn is shown in FIG 4, and a schematic diagram of the strain-stress curve when stretched at a temperature of Tn+20° C. is shown in FIG 5. Reference numeral 10 denotes the strain-stress curve in the tensile test, reference numeral 11 denotes the inflection point (upper yield point) in differential analysis, and reference numeral 12 denotes the magnitude of permanent strain.

[0062] In the tensile test of laminated film, in addition to the stretching conditions of the laminated film (elongation and tension), physical property information such as the elongation at which the laminated film undergoes plastic deformation and remains as distortion can be obtained. Under temperature conditions (below temperature Tn [℃]) when the laminated film is not softened, that is, when the thermoplastic resins constituting the laminated film are not softened (in a glassy state), the unsoftened thermoplastic resin is forcibly stretched, and a permanent distortion (symbol 11) occurs due to the stress rising at a slight stretching ratio, and even if the film shrinks by the amount of the distortion, it cannot return to its original shape. On the other hand, under temperature conditions (above temperature Tn) when all the thermoplastic resins constituting the laminated film are softened, the thermoplastic resins can smoothly follow while changing their structure, making it possible to deform the material in a state where distortion is unlikely to remain. The point at which plastic deformation begins (referred to as the upper yield point) corresponds to the convex peak position (reference numeral 11) where the stress first increases after the start of stretching in the strain-stress curve obtained in the tensile test, and can be grasped by performing differential analysis of the obtained curve and analyzing the so-called inflection point where the slope of the peak changes from positive to negative. Thus, it is important for the shape-fixing / restoring material of the present invention that the elongation showing the permanent strain is high and the material can be restored to its original state.

[0063] In the laminated film of the present invention, it is preferable that the inflection point (upper yield point) occurs at 50% or more. As described later, the laminated film can be preferably used as a sheet material for medical, consumer, and industrial use, but a certain degree of elongation is required when it is used for industrial use by molding and following a complex shape, or when it is used for medical or consumer use by stretching and contracting to a complex shape such as a complex moving part of the human body. In particular, for medical use, an elongation of about 20 to 30% is applied even in areas other than the joints of the limbs, and a maximum elongation of about 60 to 70% is applied around the joints, so it is preferable that the film elastically deforms without plastic deformation up to these elongation ranges. From this viewpoint, the inflection point that appears in the strain-stress curve is more preferably in the region of 60% or more, and even more preferably in the region of 65% or more. In order for the inflection point to appear in the region of strain of 50% or more, it is possible to achieve this by having a multi-layer laminate structure of 9 or more layers with a large number of layers, by using a thermoplastic elastomer that has low crystallinity and is unlikely to leave permanent strain, by using a non-crystalline thermoplastic resin B that is less affected by strain, or by designing the laminate ratio low so that the proportion of thermoplastic resin B is high.

[0064] When the storage modulus of layer A at temperature T (°C) is GA(T) (GPa) and the storage modulus of layer B is GB(T) (GPa), it is preferable to satisfy 1.2GA(Tn - 10) < GB(Tn - 10) and GA(Tn + 10) ≥ 1.2GB(Tn + 10). The shape-fixing / restoring function, which is a characteristic property of the laminated film of the present invention, is based on a multilayer laminated structure, and by using a material in which a polymer with strong elastic expansion and contraction and a polymer with high rigidity are alternately laminated, the magnitude relationship between the elastic moduli of the two polymers changes around a specific temperature. This can be realized by such a design. Since the two types of polymers showing different viscoelasticities as constituent components behave as completely independent polymer layers in the material, unlike the conventional single-film technology, it is possible to exhibit a high shape-fixing amount and a high shape-restoring amount with respect to deformation in a specific direction without depending on the combination and ratio of the two types of polymers. Specifically, the shape-fixing / restoring characteristics can be exhibited by switching the function of the thermoplastic resin B, which switches from a rigid state to a molten state or a rubber-elastic state with the transition temperature Tn as the boundary temperature, as a stopper for the rubber-elastic contraction behavior of the thermoplastic resin A. The realization of this contraction-switching function is obtained from the magnitude relationship between the storage moduli of the thermoplastic resins constituting the laminated film. That is, in the temperature region lower than the temperature Tn, the storage modulus of the thermoplastic resin B showing rigidity in the glass state is significantly higher than that of the thermoplastic resin A that can exhibit elastic expansion and contraction behavior, so that the shape can be fixed by repelling the elastic expansion and contraction behavior of the thermoplastic resin A. On the other hand, in the temperature region higher than the temperature Tn, for the thermoplastic resin A showing elastic expansion and contraction behavior, since the thermoplastic resin B shows a molten state or rubber-like behavior and its elastic modulus decreases, the shape can be restored by the automatic action of the contraction of the thermoplastic resin A, and a shape can be imparted by applying an external force. However, since this conversion of the mechanical behavior does not change dramatically at the boundary of the temperature Tn, the elastic modulus difference in the temperature regions of Tn - 10°C and Tn + 10°C is defined here. The storage modulus of each layer in the state of the laminated film is obtained by the peak force tapping method of an atomic force microscope with respect to the cross section of the laminated film.Specifically, a silicon cantilever is moved vertically, repeatedly pressed against the cross section and then released, sweeping the cross section, and the elastic modulus of each thermoplastic resin layer is analyzed based on the force curve obtained.

[0065] Under the temperature condition of Tn-10°C where the shape fixing function works, it is preferable that the storage modulus GB(Tn-10) of the thermoplastic resin B layer is greater than 1.2 times the storage modulus GA(Tn-10) of the thermoplastic resin A. If the difference in modulus is not greater than 1.2 times, the thermoplastic resin B cannot suppress the elastic shrinkage behavior of the thermoplastic resin A, so that the shape is changed and the stress is released, and then the shrinkage by the thermoplastic resin A works, which may cause a problem of a decrease in the dimensional fixation rate. In order to enhance the shape fixing ability from the resin characteristics, it is more preferably 4.0 times or more, and more preferably 10 times or more. On the other hand, under the temperature condition Tn+10°C which contributes to shape imparting and shape restoration, it is preferable that the storage modulus GA(Tn+10) of the thermoplastic resin A layer is greater than 1.2 times the storage modulus GB(Tn+10) of the thermoplastic resin B so that the laminated film can easily deform with low stress. If the elastic modulus of thermoplastic resin A at the temperature is lower than 1.2 times, the repulsion against the shape change by thermoplastic resin B during deformation is strong, so that the material is forced to deform during molding, and distortion is likely to remain in the material. In addition, if the difference in elastic modulus is small, it is considered that both thermoplastic resins are in a similar polymer state, especially a rubber-like state, and the dimensional fixation rate may be low. In order to increase the shape recovery ability, it is more preferably 2.0 times or more, and even more preferably 3.0 times or more. All of these are derived from the characteristics of the thermoplastic resin, and it is important to select a thermoplastic resin that exhibits the desired elastic modulus, but in order to increase the elastic modulus difference in order to fully exert the shape fixation ability, it can be achieved by selecting a highly rigid amorphous resin as thermoplastic resin B.

[0066] In the laminated film of the present invention, it is preferable that the Tm and Tn satisfy Tm-Tn≧30°C. Tm-Tn as described here refers to the temperature range from the melting point of the crystalline resin to the shape conversion point, and indicates the temperature range in which shape change and shape restoration are possible since the thermoplastic resin A exhibits rubber elastic behavior while the thermoplastic resin B is softened or melted. The small temperature range may cause the laminated film to show a sheet shape but not be able to fully exhibit the shape restoration function, since the resin melts before the shape restoration due to the contraction of the thermoplastic resin A is completed at a temperature exceeding the shape conversion point Tn. Therefore, in order to obtain a laminated film with a shape restoration function, it is preferable to keep the temperature range from the shape conversion point Tn to the melting point Tm of the crystalline thermoplastic resin A constituting the laminated film as large as possible, more preferably 50°C or more, and even more preferably 85°C or more. This is due only to the resin characteristics, and can be achieved by selecting the melting point and glass transition temperature of the thermoplastic resin to be laminated in consideration of the melting point.

[0067] The laminated film of the present invention preferably has two or more loss tangent peaks when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz in the temperature range from -80°C to the melting point Tm, and the relationship between the loss tangent peak tanδ1 occurring at the lowest temperature (temperature T1 (°C)) and the loss tangent peak tanδ2 occurring at the highest temperature (temperature T2 (°C)) is tanδ2 / tanδ1≧1.0. The loss tangent mentioned here can be expressed as the ratio of the loss modulus (G″) to the storage modulus (G′) when dynamic viscoelasticity measurement is performed on the laminated film at the above-mentioned frequency, and indicates a temperature range where the energy absorption amount of the laminated film is large, that is, a temperature range where the viscoelastic change of the material is more significant. The temperature where the viscoelastic change is significant generally corresponds to the temperature at which the phase transition occurs between the glass state, the rubber state, and the molten state, such as the glass transition temperature or melting point of the thermoplastic resin constituting the material.

[0068] An example of a loss tangent spectrum in dynamic viscoelasticity measurement obtained for the laminated film of the present invention is shown in Figure 6. In Figure 6, reference numeral 13 denotes the loss tangent tan δ spectrum obtained by dynamic viscoelasticity measurement, reference numeral 14 denotes temperature T1 [°C], reference numeral 15 denotes the loss tangent peak occurring at the lowest temperature, reference numeral 16 denotes temperature T2 [°C], reference numeral 17 denotes the loss tangent peak occurring on the highest temperature side in the temperature range lower than the melting point Tm, reference numeral 18 denotes tan δ1, reference numeral 19 denotes tan δ2, and reference numeral 20 denotes the loss tangent peak occurring at a temperature different from temperatures T1 and T2.

[0069] In addition, although not shown in the figure, there are cases where the tan δ peaks are close to each other and overlap with each other, resulting in some spectra being obtained as shoulder peaks rather than clear independent peaks with peak tops. In such cases, the spectrum slope at each temperature is calculated by differential analysis of the obtained tan δ spectrum, and the temperature at which the slope is greatest when the slope changes from a decreasing trend to an increasing trend and then to a decreasing trend, or the temperature at which the slope is greatest when the slope changes from an increasing trend to a decreasing trend and then to an increasing trend, is defined as the temperature corresponding to the shoulder peak.

[0070] In the laminated film of the present invention, which is made of a plurality of different thermoplastic resins, if the melting point Tm is derived from the crystalline thermoplastic resin A, in the temperature range lower than the melting point Tm, in addition to the glass transition temperature derived from the thermoplastic resin A, a tan δ peak appears at the glass transition temperature when the thermoplastic resin B is an amorphous resin, and at the temperature corresponding to the glass transition temperature and the melting point when the thermoplastic resin B is a crystalline resin, and at least two or more loss tangent peaks appear. In the case of a single-layer film using a conventional kneaded and dispersed polymer, if the compatibility of the two types of thermoplastic resins to be combined is good and both resins are well finely dispersed, the material behaves as a single resin material macroscopically, and only one tan δ peak appears at the glass transition temperature other than the melting point, so that this is not applicable. In other words, this tendency can be confirmed characteristically in a material that shows a sea-island structure due to poor dispersion, or in a multilayer laminated film such as the present invention.

[0071] In the laminated film of the present invention, among the loss tangent peaks appearing at two or more points, when the peak appearing at the lowest temperature (temperature T1 ° C.) in the temperature range below the melting point Tm (temperature T2 ° C.) is tan δ1, and the peak appearing at the highest temperature (temperature T2 ° C.) is tan δ2 / tan δ1 ≧ 1.0 is preferable. Temperature T2 corresponds to the shape change point Tn of the laminated film in the description of the differential calorimeter measurement, and corresponds to the glass transition temperature (in the case of an amorphous resin) or melting point (in the case of a crystalline resin) derived from thermoplastic resin B. Temperature T1 is the temperature that appears at the lowest temperature and indicates the glass transition temperature of thermoplastic resin A or B. In particular, considering the preferred thermoplastic resin configuration of the laminated film of the present invention, that is, that thermoplastic resin A is a crystalline thermoplastic elastomer and thermoplastic resin B is an amorphous or crystalline thermoplastic resin, temperature T1 generally corresponds to the glass transition temperature derived from thermoplastic resin A due to the characteristics of the resin used. The spectrum corresponding to symbol 20 depends on the crystallinity of the thermoplastic resin used, and therefore often does not exist when an amorphous resin is used as a resin with high rigidity.

[0072] Among the multiple tan δ peaks thus appearing, the tan δ peak position with the highest peak intensity indicates the most characteristic phase transition state of the material. Since the laminate film of the present invention is characterized by being a material that converts between shape fixation and shape change / restoration functions at the shape conversion point Tn, it is preferable that tan δ at temperature T2 shows the highest peak intensity and shows tan δ2 / tan δ1≧1.0. More preferably, it is 3.0 or more, and even more preferably 4.0 or more. When tan δ2 / tan δ1 shows less than 1, the laminate film has a strong elastic behavior derived from thermoplastic resin A (thermoplastic elastomer), so the effect of elastic shrinkage behavior as a laminate film is strong, and the material does not sufficiently obtain shape fixation / restoration function at temperature Tn. In order to achieve tan δ2 / tan δ1≧1.0, it can be achieved by a laminate film with a large number of layers in a multilayer laminate structure and no lamination disorder, thermoplastic resin B being an amorphous resin, and the lamination ratio being small and the amount of amorphous resin components being large.

[0073] The laminate film of the present invention is preferably a laminate film that can be used in applications requiring shape fixing and shape recovery properties. More specifically, the laminate film can be suitably used in applications requiring the ability to fix (retain) a shape, such as a bent shape, at a temperature equal to or lower than the Tn and to restore the fixed shape at a temperature exceeding the Tn.

[0074] More specifically, the laminated film of the present invention can be suitably used in various applications requiring particularly high flexibility and stretchability, taking advantage of its excellent flexibility, stretch response, and heat resistance. For example, it can be suitably used for electronic device materials such as smartphone housings, touch panels, color filters, flat panel displays, flexible displays, flexible devices, wearable / wearless devices, and sensors, in-vehicle materials such as mirrors, window members, dashboards, car navigation touch panels, room mirrors, and windows, and for various printed materials, medical films, sanitary material films, agricultural films, building material films, clothing materials, and the like, as surface materials, internal materials, constituent materials, and manufacturing process materials. In particular, the laminated film of the present invention can be suitably used as an electronics device circuit material in which an electric circuit such as a stretchable sensor is laminated by imparting adhesion to the printed layer, or as a substrate for a wearable / wearless sensor or a medical film substrate by applying a material with high water vapor permeability such as a polyurethane resin.

[0075] The laminated film of the present invention can be preferably used for sensor applications in which an elastic conductive layer is laminated. As the demand for wearable devices with health care functions increases with the expansion of health consciousness, wearable devices feel like they are being worn, and resistance to wearing them for long periods of time is increasing. In the midst of this, the need for wearless devices that can be used without feeling like they are being worn is increasing, and sensor devices for measuring vital signs (brain waves, pulse, veins, etc.) that can be attached directly to the skin, etc., are attracting attention. As such sensor members, elastic electronic board circuits are applied, and due to the characteristic that the electrical resistance does not change even when deformed, those that can be used even when wrapped around the human body, etc. are being considered. In addition, by incorporating a touch sensor element on the surface of the laminated film of the present invention, it can be developed as a display material as a film-like device that can input characters, etc. As such sensors, electrostatic capacitance sensors that are inexpensive, lightweight, and can be made thin may be used, and resistance sensors, piezo sensors using piezoelectric polymers, energy harvesting sensors using triboelectric charging, etc. may be used. In particular, sensor materials laminated with such stretchable conductive layers can be used not only for the vital signs sensor applications mentioned above, but also for slimming down integrated circuits by bonding them to curved plastic materials, or as flexible film materials that contribute to making electronic component modules smaller and thinner.

[0076] Since the above-mentioned sensor is preferably used within the temperature range of body temperature or the display, it is particularly preferable that the shape or function can be changed for use within a temperature range of 20 to 100° C. Note that changing the function refers to changing the function obtained as a laminate film by changing the mechanical and optical properties by changing the overall or partial shape of the laminate film.

[0077] The sensor that can be used by changing its shape at the above temperature may be a sensor that softens in the above temperature range and is used continuously in the softened state by touching the temperature, or a type of sensor that changes its shape at a specific temperature (shape change point Tn) or higher, is installed so as to follow a predetermined shape, and then is solidified by lowering the temperature. For example, when a material having a stretchable conductive layer laminated thereon is used as a vital sensor, the device stretches in response to the movement of the body after being worn, but if it is a sensor for monitoring heart rate, pulse, body temperature, etc. like current wearable terminals, it can be used by following the shape by stretching up to about 20 to 30% on the arm or chest. On the other hand, an elongation rate of more than 50% may be required in the joint part. In that case, the film material of the present invention that shows elastic deformation even at an elongation rate of 50% or more and is less likely to retain distortion can be suitably used. Examples of applications requiring an elongation rate of 50% or more include sensor materials that measure the movement behavior of artificial joints and sensor materials equipped with acceleration sensors for monitoring daily movements. It is also suitable for use as a biosensor with a power storage function that utilizes a piezoelectric sensor that responds with high sensitivity to distortion and vibration caused by joint movements. Such a sensor may be a material in which a conductive layer is directly laminated onto a film, or a material consisting of a combination of a sensor portion that has been given conductivity and a base film that comes into direct contact with the skin.

[0078] As an example of a sensor whose function can be changed by changing the temperature, there is a sensor material whose light transmittance, diffusion, and light collection can be switched by changing the surface shape. In this case, it can be expressed by performing a surface treatment having a certain shape in the depth direction from the outermost surface of the laminated film over 10 to tens of layers. For example, by providing a rounded convex surface shape as a surface treatment, it can be used as a material that changes the angle of incidence of light from the outside and collects light, or by providing a pointed convex surface shape, it can be used as a material that diffuses light from the outside / inside. It is expected that the surface shape can be converted to a flat shape by softening it at a certain temperature or higher and deforming it by applying pressure from the outside to crush the shape, and that the material can be switched to a material with high parallel light transmittance. Furthermore, when a thermal stimulus of a certain temperature or higher is applied, it can be restored to the original surface-treated shape. In this way, by using the laminated film having a highly stimuli-responsive multilayer laminated structure of the present invention, it can be expected to be used as a sensor that can be used repeatedly as a light sensor material.

[0079] The laminated film of the present invention is preferably used as a tape with a urethane-based or silicone-based adhesive layer on at least one side of the laminated film as a substrate for use in a medical film or a film for sanitary materials, which is to be applied to the human body. Examples of adhesives include acrylic adhesives, urethane-based adhesives, silicone-based adhesives, and rubber-based adhesives. As a tape substrate for use in application to the human body, it is preferable to use urethane-based adhesives, which are less irritating to the skin and have excellent air escape properties and removability, and silicone-based adhesives, which are more adhesive and have less effect on dry skin, than acrylic adhesives, which have strong adhesive power and cause great damage to the skin when peeled off, and rubber adhesives, which are of concern for allergy. These adhesives may be directly laminated to the laminated film substrate, or, in order to improve adhesion, a primer layer that improves adhesion may be provided in advance on the surface of the laminated film, and an adhesive layer may be provided directly on the primer layer.

[0080] This type of tape can be used by sticking it to a flat surface with an adhesive like a normal bandage, but since it has the particular feature of being able to change and restore its shape even when applied to areas with high elasticity, it can be ideally used as a joint support tape, sports tape, or fixation tape for sprains and fractures, etc., as a tape that can be used repeatedly while changing its shape according to the progress of treatment, etc.

[0081] Such tapes have a water vapor transmission rate of 300(g·25μm / (m 2 ·day)) or higher, and the material should preferably be one that can be used by changing its shape and function in a temperature range of 20 to 50°C. Since it is preferable for the tape base material to be one that can be applied to the human body and used for long periods of time by changing its shape, it is required to have a water vapor transmission rate that does not interfere with skin breathing at the site where the tape is applied. In addition, the tape base material is preferably required to have a property that it can be fixed in shape to conform to the human body and can be easily removed, and it is preferable for the tape to exhibit shape fixation / recovery behavior in a temperature range of 50°C or less where human skin does not feel hot even when touched for long periods of time. In addition, the water vapor transmission rate should be 800(g·25μm / (m 2 It is preferable that the period is longer than 10 days.

[0082] Next, a preferred method for producing the laminated film of the present invention will be described below, although it is needless to say that the present invention is not limited to such an example.

[0083] The thermoplastic resins constituting each thermoplastic resin layer of the laminated film are prepared in the form of pellets or the like. The pellets are dried in hot air or under vacuum as necessary, and then fed to separate extruders. When additives are added to the thermoplastic resin, powder, granule, or liquid additives may be kneaded and dispersed in a desired ratio during the main extrusion process by a top feed or side feed method, or master pellets in which the additives have been dispersed in the thermoplastic resin in advance may be fed. In the extruder, the thermoplastic resin is heated and melted to a glass transition temperature or above in the case of an amorphous thermoplastic resin, or to a melting point or above in the case of a crystalline thermoplastic resin, and the extrusion amount of each thermoplastic resin is made uniform by a gear pump or the like, and foreign matter and modified resins are removed through a filter or the like. These thermoplastic resins are formed into a desired laminate through a lamination device, and then discharged from a die in the form of a sheet. The molten sheet discharged from the die is then extruded onto a cooling body such as a casting drum, where it is cooled and solidified to become a cast sheet. Casting At this time, it is preferable to use a wire-shaped, tape-shaped, needle-shaped, or knife-shaped electrode to bring the thermoplastic resin into close contact with a cooling body such as a casting drum by electrostatic force, and rapidly solidify the resin. Also preferred are methods in which air is blown from a slit-shaped, spot-shaped, or planar device to bring the sheet into contact with a cooling body such as a casting drum and then rapidly solidify the sheet, or methods in which the sheet is rapidly solidified by bringing the sheet into contact with a cooling body using a nip roll. As an auxiliary, a liquid with good wettability such as liquid surfactant water or liquid paraffin can be applied to the surface of the casting drum to provide adhesion. Furthermore, when it is difficult to bring the molten sheet into contact with the cast and then solidify the sheet by electrostatic force, another preferred method is to introduce the molten sheet into two rolls provided with a specific gap therebetween and then cool and solidify the sheet from both sides.

[0084] As described above, the laminated film of the present invention preferably uses a crystalline thermoplastic resin with a low glass transition temperature as the outermost layer, but the resin disposed on the outermost surface of the laminated film may exhibit tackiness and may easily adhere to the casting drum. Therefore, it is preferable to apply a release agent (fluorine-based, silicon-based, wax-based, etc.) to the surface of the casting drum, or to use a matte roll or a fluorine roll as the roll material.

[0085] As the multi-layer lamination device, a multi-manifold die, a feed block, a square mixer, etc. can be used, but in particular, in order to efficiently obtain the multi-layer laminate of the present invention, it is preferable to use a feed block having a fine slit. When such a feed block is used, the device does not become extremely large, so the amount of foreign matter generated due to thermal deterioration is small, and high-precision lamination is possible even when the number of layers is extremely large. In addition, the lamination accuracy in the width direction is also significantly improved compared to the conventional technology. Furthermore, this device has the advantages that the thickness of each layer can be adjusted by the shape (length, width) of the slit, making it easy to achieve any layer thickness, and that the effect of the resin flow during the lamination process makes it easy to orient particles in the direction of the laminated sheet surface.

[0086] When a laminated sheet is produced using a slit-type feedblock, the thickness and distribution of each layer can be adjusted by adjusting the pressure balance by changing the length and width of the slit. The length of the slit refers to the length of the comb teeth that form the flow path for alternately flowing layers A and B inside the slit plate. In addition, after forming a laminate in the feedblock, a method can be used in which the number of layers is doubled by stacking them through a square mixer to increase the number of layers.

[0087] The obtained cast sheet may be subjected to the following stretching step as required to remove distortion of the laminated sheet in advance to suppress deformation after use or to utilize the shrinkage behavior so that it can be used immediately. The stretching step may involve uniaxial stretching in a specific direction, either the longitudinal direction (the conveying direction in the manufacturing process of the laminated sheet) or the transverse direction, or biaxial stretching in the longitudinal direction and the transverse direction. When biaxial stretching is performed, it may be performed biaxially sequentially or simultaneously.

[0088] First, uniaxial stretching and sequential biaxial stretching in which the sheet is stretched in the longitudinal direction and then in the width direction will be described. Here, stretching in the longitudinal direction refers to uniaxial stretching for giving the sheet a molecular orientation in the longitudinal direction, and is usually performed by the difference in peripheral speed of the rolls. This stretching may be performed in one stage, or in multiple stages using a plurality of pairs of rolls. The stretching ratio varies depending on the type of resin, but in the present laminated film, the layer stretching ratio is preferably 1.1 to 3.0 times, and particularly preferably 1.1 to 2.0 times. If the ratio is increased, the influence of permanent deformation of the thermoplastic resin is likely to occur, and since the influence on the dimensional recovery rate is large, the stretching ratio is preferably within the above-mentioned preferred stretching ratio range. In addition, the stretching temperature is preferably set within the range of the glass transition temperature +10°C to the glass transition temperature +100°C of the resin constituting the sheet. The uniaxially stretched laminated sheet obtained in this manner can be subjected to surface treatment such as corona treatment, frame treatment, and plasma treatment as necessary, and then a primer layer can be formed to improve adhesion with the film to be laminated on the upper part. In the in-line coating process, the primer layer may be applied to one side or to both sides simultaneously or one side at a time.

[0089] The stretching in the width direction means stretching for giving the sheet a width direction orientation, and is usually performed by conveying the sheet while holding both ends with clips using a tenter. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 3.0 times, and particularly preferably 1.1 to 2.0 times. The stretching temperature is preferably the glass transition temperature + 10°C to the glass transition temperature + 100°C of the resin constituting the sheet and not more than the melting point Tm.

[0090] Next, the case of simultaneous biaxial stretching will be described. In the case of simultaneous biaxial stretching, the obtained cast sheet may be subjected to surface treatment such as corona treatment, frame treatment, plasma treatment, etc., as necessary, and then functions such as easy slip, easy adhesion, and antistatic properties may be imparted by in-line coating. In the in-line coating process, the coating layer may be applied to one side of the sheet, or may be applied to both sides simultaneously or one side at a time.

[0091] Next, the cast sheet is introduced into a simultaneous biaxial tenter, and conveyed while both ends of the sheet are held by clips, whereby the sheet can be stretched simultaneously and / or stepwise in the longitudinal and transverse directions. The simultaneous biaxial stretching machine (tenter) may be of the pantograph type, screw type, drive motor type, linear motor type, etc., but the drive motor type or linear motor type, which can change the stretching ratio at any desired position and can perform relaxation treatment at any desired position, is preferred. The stretching ratio varies depending on the type of resin, but is usually preferably 1.1 to 4.0 times as an areal ratio, and more preferably 1.1 to 2.0 times. The stretching speed may be the same or different speeds in the longitudinal and transverse directions. The stretching temperature is preferably the glass transition temperature of the resin constituting the alternating laminate unit +10°C to the glass transition temperature +100°C.

[0092] The laminated film obtained in the above manner is trimmed to a required width by a winding device and wound in a roll state so as to prevent wrinkles from forming during winding. In addition, embossing may be performed on both ends of the film to improve the roll shape during winding.

[0093] The thickness of the laminated film of the present invention is not particularly limited, but considering the trend toward thinner functional films, stable cast film-forming speed, and the expected applications of base films for medical, industrial, and consumer use, it is preferably 20 μm or more and 1 mm or less. Considering roll winding properties, it is more preferably 500 μm or less. Although there is no lower limit, in order to ensure stable roll winding properties even under high-speed casting conditions and to form a film without tearing, it is practically preferable for the thickness to be 20 μm or more.

[0094] The thickness of the laminated film is not particularly limited, but it is preferable to adjust the thickness by increasing or decreasing the lip gap of the die, the take-up speed of a cooling body such as a casting drum, etc. In order to suppress the film width shrinkage caused by an increase in the take-up speed, it is preferable to appropriately adjust the gap between the die and the cooling body. When the film width cannot be kept constant, for example, the stretch ratio in the width direction can be made constant by adjusting the distance between the clips in the tenter.

[0095] In addition, a functional layer for adding functions such as scratch resistance and abrasion resistance may be laminated on the outermost surface of the laminate film of the present invention. When the laminate film is transported roll-to-roll in the film-forming transport process or processing process, the occurrence of scratches on the laminate film surface due to friction between the roll and the film can be prevented. In addition, in consideration of improving weather resistance and suitability for use, an ultraviolet absorbing layer, an adhesive layer, a gas barrier layer containing metal oxides, etc., a release (anti-tackiness) layer, a printing layer, a conductive layer, etc. may be formed. These layers may be one layer or multiple layers, and one layer may have multiple functions. EXAMPLES

[0096] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. Each characteristic was measured by the following methods.

[0097] (Methods for measuring characteristics and evaluating effects) The methods for measuring the characteristics and evaluating the effects of the present invention are as follows.

[0098] (1) Differential scanning calorimetry (DSC) A differential scanning calorimeter EXSTAR DSC6220 manufactured by Hitachi High-Technologies Corporation was used. Measurements and temperature readings were performed in accordance with JIS-K-7122 (1987). Specifically, when approximately 5 mg of a sample was placed on an aluminum tray and heated at a rate of 20°C / min in the temperature range from -80°C to 280°C, the glass transition temperature (°C) was determined as the temperature corresponding to the inflection point of the step transition, and the melting point Tm (°C) corresponding to the endothermic peak was determined. In addition, the measurement of each layer was performed in the same manner by peeling and extracting only the portion of each layer.

[0099] (2) Acquire a cross-sectional image of the laminate (when the layer thickness is 5 μm or more) The layer structure information of the laminated film was obtained by observing the samples sliced ​​using an ultramicrotome with a digital microscope according to the thickness of each layer. Specifically, a Keyence VHX-5000 digital microscope was used, equipped with a lens that allows observation at a maximum magnification of 1000x, to obtain cross-sectional images to analyze the layer structure (number of layers, regular arrangement, layer thickness distribution) and the thickness of each layer.

[0100] (3) Acquiring a cross-sectional image of the laminate (when the layer thickness is less than 5 μm) The layer structure information of the laminated film was obtained by observing the sample sliced ​​using an ultramicrotome with a transmission electron microscope (TEM) according to the thickness of each layer. Specifically, a transmission electron microscope JEM-1400 Plus (manufactured by JEOL Ltd.) was used to observe the cross section of the laminated film (thickness direction, i.e., cross section perpendicular to the film surface) at an acceleration voltage of 100 kV, and the layer structure (number of layers, regular arrangement, layer thickness distribution) and each layer thickness were analyzed by obtaining a cross-sectional image. In addition, a staining technique using an electronic staining agent (RuO4, etc.) was used to obtain a large contrast difference between each layer. In addition, according to the thickness of each layer, observation was performed at a direct magnification of 40,000 times when the thin film layer thickness was less than 100 nm, at a direct magnification of 20,000 times when the thin film layer thickness was 100 nm or more and less than 500 nm, and at a direct magnification of 1,000 to 10,000 times when the thin film layer thickness was 500 nm or more.

[0101] (4) Layer thickness analysis The cross-sectional image obtained in this transmission electron microscope observation was converted into a compressed image file (JPEG), and position-brightness data was obtained by line profile along the thickness direction of the laminated film using ImagePro-10 manufactured by MediaCybernetics. Then, a five-point moving average process was performed on the profile obtained by plotting the relationship between position and brightness using a spreadsheet software (Microsoft Corporation "Excel" (registered trademark) 2016). The average process was performed by performing an average process of brightness for five consecutive measurement positions, changing the position one point at a time and continuously processing the same calculation, and an averaged position-brightness profile was obtained. In the obtained averaged position-brightness profile, the position surrounded by the inflection points where the slope changes from positive to negative or negative to positive was determined to be one layer. For each layer obtained by this method, position-brightness data was then obtained in the planar direction (direction perpendicular to the thickness direction) of the laminated film. After calculating the average value and standard deviation of the brightness obtained for each layer, if the difference between the average values ​​of the brightness of the two adjacent layers was greater than any of the standard deviations of the brightness of the adjacent thermoplastic resin layers, these two adjacent layers were determined to be different. At this time, the difference (distance) in the positions between the inflection points was calculated as the layer thickness of each layer.

[0102] (5)Lamination ratio The lamination ratio of the laminate film was calculated using the layer thickness of each layer calculated by the methods described in (2) to (4). Specifically, the total value of the layer thicknesses of each layer exhibiting the same contrast contained in the laminate film was calculated, and the total value of the layer thickness of layer A relative to the total layer thickness of layer B contained in the laminate film was calculated as the lamination ratio.

[0103] (6) AFM tapping elastic modulus measurement The cross-section of the sample cut using an ultramicrotome was evaluated using a Bruker scanning probe microscope NanoScopeV. The laminated film was heated to the desired temperature in a thermostatic chamber, and the silicon cantilever NCHR was used as a probe. The cantilever was moved vertically continuously in the thickness direction of the laminated film in peak force tapping mode, and measurements were taken at a sweep speed of 0.3 to 0.5 Hz / s to obtain continuous change data on the elastic modulus (storage modulus, loss modulus). The storage modulus or loss modulus of each layer was determined by judging the distribution of the "different" thermoplastic resin layers and the entire laminated film, and then the elastic modulus data of five layers selected from the same thermoplastic resin layers present was averaged. The tan δ of each layer at a specific temperature was calculated by dividing the loss modulus measured at that temperature by the storage modulus.

[0104] (7) Loss tangent (tan δ) analysis by dynamic viscoelasticity measurement Based on the tensile vibration non-resonance method of JIS K7244-4 (1999) (this is called the dynamic viscoelasticity method), a loss tangent spectrum was obtained using a dynamic viscoelasticity measuring device DMS6100 manufactured by Seiko Instruments Inc. The detailed measurement conditions were as follows: Measurement mode: "Tension", chuck distance: "20 mm", specimen width: "10 mm", frequency: "10 Hz", strain amplitude: "10 μm", minimum tension: "20 mN", initial force amplitude: "40 mN", measurement temperature: "-80°C to Tm°C", heating rate: "2°C / min".

[0105] (8) Water vapor permeability Measurements were performed using the cup method in accordance with JIS Z 0208. Approximately 20 g of anhydrous calcium chloride was used as the moisture absorbent, and placed in a pre-weighed aluminum cup with an inner diameter of 6 cm, which was then covered with a laminated film and secured around the periphery with a specified O-ring to seal the cup without any gaps. A total of three completed aluminum cups were created and placed in a constant temperature and humidity chamber controlled at 40°C and 90% RH. The mass increase after three days was analyzed to determine the daily water vapor transmission rate (g·25μm / (m 2 ·day) was calculated.

[0106] (9) Electron energy loss spectroscopy (EELS) A cut sample of the cross section (thickness direction cross section) of the measurement target was prepared by ultra-thin sectioning using an ultramicrotome. The dielectric constant of the cut sample was measured using an atomic resolution analytical electron microscope ARM200F manufactured by JEOL. Specifically, after acquiring a HAADF-STEM (High Angle Annular Dark-Field Scanning Transmission Electron Microscopy) image at an acceleration voltage of 80 kV and a beam spot size of 0.2 mmφ, a multi-point analysis (60 × 60 pixels, 20 nm / pixel) was performed on the layer to be measured in 50 msec to obtain data on energy loss and electron beam intensity. The same operation was performed on three points for the same thermoplastic resin layer in the laminated film to obtain spectrum data with improved S / N ratio. From the obtained spectrum data, background correction due to elastic scattering and removal of multiple scattering effects were performed, and the dielectric function of each layer was calculated by the Kramers-Kronig transformation shown in formula (4). The integral range during Kramers-Kronig transformation was set to 0 to 200 eV. Based on the dielectric function of equation (4), the real and imaginary parts of the dielectric constant were calculated from equations (5) and (6), respectively, and then the dielectric constant was calculated from the square root of the sum of the squares of these, as shown in equation (7). Using the above method, the dielectric constant at a loss energy of 2.5 eV of each thermoplastic resin layer was calculated.

[0107] In formulas (4) to (7), Re is the real part, Im is the imaginary part, ε is the dielectric constant (average value), ε(ω) is the dielectric function, ε1 is the real part of the dielectric constant, ε2 is the imaginary part of the dielectric constant, and ω and ω' are angular frequencies.

[0108]

number

[0109]

number

[0110]

number

[0111]

number

[0112] (10) Dimensional fixation rate, dimensional recovery rate ("50% stretch molding - reheat cycle test") The laminated film was cut into strips with a width of 1 cm and a length of 15 cm, and a mark was placed in the center 10 cm. The exact distance between the marks (d [mm]) was measured using a Nikon V-16A projector. Five samples with the measured length were stretched in the longitudinal direction at 1.5 times (50% strain) after preheating for 60 seconds in a stretch zone set to Tn + 20 ° C of the laminated film using a Bruckner stretcher KARO-V. The stretched sample was returned to the insert position, held by the clip for 30 seconds, and then released to obtain a stretched sample. The distance between the marks (d1 [mm]) of the obtained stretched sample was measured using a projector. Next, the obtained sample was heat-treated for 1 minute under a hot air oven at Tn + 20 ° C without load, the distance between the marks d2 of the obtained sample was measured, and the dimensional fixation rate and dimensional recovery rate were calculated according to formulas (2) and (3). The average values ​​obtained were used as the dimensional fixation rate and dimensional recovery rate in the first cycle test. This cycle of 1.5 times stretching, cooling and solidifying, and reheating is referred to as the "50% stretch molding-reheating cycle test."

[0113] This cycle test was repeated five times for the same sample, and when the distance between the marks before the start of the fifth cycle test was d3, the distance between the marks after the fifth 50% stretching and cooling was d4, and the distance between the marks after the fifth cycle test was d5, the dimensional fixation rate and dimensional recovery rate after the five cycle tests were calculated according to formulas (8) and (9). The values ​​calculated for each of the five samples were averaged and used as the dimensional fixation rate and dimensional recovery rate values ​​in the fifth cycle test.

[0114]

number

[0115]

number

[0116]

number

[0117]

number

[0118] (11) Formability In five stretching and cooling tests using the stretcher tester described in (10), the adhesion to the clips and the stretching unevenness of the laminated film were judged as follows: For stretching unevenness, the thickness was measured at five points: the center of the strip sample, the center of the marked area, and the midpoint between the center of the marked area and the center of the strip sample. The standard deviation / average value of the thickness was calculated as the unevenness value, and it was judged whether the unevenness value before and after stretching differed by 3% or more. ◯: No adhesion to the clip, small thickness unevenness, and uniform stretchability ×: The film stuck to the clip and could not be stretched without a crystalline stretching auxiliary film, or, although there was no sticking, the thickness was uneven by 3% or more and uniform stretching was not possible.

[0119] <Thermoplastic resin> Resin 1: Polytetramethylene ether glycol copolymerized polyethylene terephthalate resin with a glass transition temperature of -60°C and a melting point of 160°C Resin 2: Thermoplastic polyurethane resin with a glass transition temperature of -50°C and a melting point of 155°C Resin 3: Polyether block amide resin with a glass transition temperature of -65°C and a melting point of 144°C Resin 4: Polyethylene terephthalate resin copolymerized with 33 mol% cyclohexanedimethanol, exhibiting a glass transition temperature of 70°C Resin 5: Polyethylene terephthalate resin copolymerized with 20 mol% adipic acid and 10 mol% isophthalic acid, which has a glass transition temperature of 40°C. Resin 6: Polycaprolactone resin with a glass transition temperature of -65°C and a melting point of 60°C Resin 7: Polyvinyl alcohol resin with a glass transition temperature of 40°C and a melting point of 164°C Resin 8: 28% ethylene vinyl acetate copolymer resin with a glass transition temperature of -42°C and a melting point of 81°C. Example 1 Resin 1 and resin 4 were used as the thermoplastic resins constituting the thermoplastic resin layers A and B, respectively. Each of the prepared thermoplastic resins was fed in pellet form into two separate twin-screw extruders, melted at 260°C and 270°C, respectively, and kneaded. The kneading conditions were set so that the screw rotation speed relative to the discharge amount was 0.7 in all cases. Next, after passing through seven FSS-type leaf disc filters, the mixture was joined in a feed block with nine slits, whose temperature was adjusted to 270°C, while being metered with a gear pump, to form a nine-layer laminate with a lamination ratio of 1.0, laminated in a regular arrangement of (AB)n in the thickness direction, and both surface layers being A layers. The feed block with nine slits used here was designed so that the thickness of both surface layers was 10 times that of the remaining layers. The molten laminate that passed through the feed block was then fed to a T-die and molded into a sheet, after which it was quenched and solidified on a casting drum coated with a silicone-based release agent while applying an electrostatic voltage of 8 kV with a wire, with the surface temperature kept at 10°C, to obtain an unstretched laminate sheet. The casting drum speed was then increased and adjusted so that the laminate film thickness was 250 μm, obtaining the desired laminate film. The evaluation results of the obtained laminate film are shown in the table.

[0120] Comparative Example 1 A laminate film was obtained in the same manner as in Example 1, except that a resin obtained by mixing Resin 1 and Resin 4 in a mass ratio of 50:50 was used as the thermoplastic resins constituting the thermoplastic resin layers A and B, and the extrusion temperature was 270° C. The evaluation results of the obtained laminate film are shown in the table.

[0121] (Comparative Examples 2 and 3) A laminate film was obtained in the same manner as in Comparative Example 1, except that a resin obtained by mixing Resin 1 and Resin 4 in the mass ratio shown in the table was used as the thermoplastic resin constituting each of the thermoplastic resin layers A and B. The evaluation results of the obtained laminate film are shown in the table.

[0122] (Examples 2 to 11, Comparative Example 4) A laminate film and a molded product were obtained in the same manner as in Example 1, except that the number of layers in the feed block and the extruder output (thickness ratio within the regular arrangement) were changed as shown in the table. The feed blocks with different numbers of layers were all designed so that the surface layer was 10 times thicker than the other layers. The evaluation results of the obtained laminate film are shown in the table.

[0123] Example 12 In comparison with Example 2, three square mixers capable of doubling the number of layers by dividing the molten laminate in the center and overlapping them were combined directly below the 51-layer feed block. Theoretically, the 51-layer molten laminate forms a laminate with a layering ratio of 1.0 having 401 layers after being extruded from the die, but the laminate film actually obtained had some disorder in the lamination of both resins, and only 381 layers could be counted. The evaluation results of the obtained laminate film are shown in the table, but due to the disorder in the lamination, the performance was inferior to that of Example 10.

[0124] (Examples 13 to 17) A laminate film was obtained in the same manner as in Example 7, except that the resins used as thermoplastic resins A and B in Example 7 were changed as shown in the table. The evaluation results of the obtained laminate film are shown in the table.

[0125] [Table 1]

[0126] [Table 2]

[0127] [Table 3]

[0128] [Table 4] [Industrial Applicability]

[0129] In the present invention, a multi-layer laminate structure is used as the basic structure, and a material having a structure in which a polymer with high elasticity and a polymer with high rigidity are alternately laminated can exhibit a high degree of shape fixation and shape recovery in response to deformation in a specific direction, regardless of the combination, compatibility, or ratio of the polymers. This makes it possible to use the material as a flexible film substrate that can be used while repeatedly deforming and recovering over a long period of time. The material can be suitably used as a sensor substrate, medical film, or film for sanitary materials, which require particularly high flexibility and stretchability. [Explanation of symbols]

[0130] 1: Spectrum showing the relationship between the depth and contrast (gray level) change in the thickness direction of a laminated film with (AB)n regular arrangement 2: Layer thickness of layer A 3: Layer thickness of layer B 4: Differential calorimetry spectrum 5: Glass transition temperature that appears in the lowest temperature range 6: Glass transition temperature appears in the region below the melting point Tm 7: Melting point Tm derived from crystalline thermoplastic elastomer 8: Temperature range between the glass transition temperature and the melting point (Tm) of this resin 9: Glass transition temperature 10: Strain-stress curve in tensile test 11: Inflection point (upper yield point) when differential analysis is performed 12: Magnitude of permanent deformation 13: Loss tangent tanδ spectrum obtained by dynamic viscoelasticity measurement 14: Temperature T1 15: Loss tangent peak occurring at the lowest temperature 16: Temperature T2 17: Loss tangent peak that occurs at the highest temperature in the temperature range below the melting point Tm 18: tan δ1 19: tan δ2 20: Loss tangent peak occurring at temperatures different from T1 and T2

Claims

1. A laminated film having a structure in which 9 or more layers of A layer made of a polymer mainly composed of thermoplastic resin A and B layer made of a polymer mainly composed of thermoplastic resin B different from said thermoplastic resin A are alternately laminated, the laminated film having a dimensional fixation rate of 80% or more after stretching and a dimensional recovery rate of 80% or more after reheating to the dimensions before the test when Tn is defined as the highest temperature among the glass transition temperatures or melting points appearing in a region lower than the highest melting point Tm obtained by differential scanning calorimetry measurement using about 5 mg of a sample at a heating rate of 20°C / min according to JIS-K-7122 (1987) + 20°C. The layer whose melting point is within ±5°C of the highest melting point Tm of the laminated film is referred to as layer A, and the layer whose glass transition temperature or melting point, whichever is higher, is within ±5°C of Tn of the laminated film is referred to as layer B.

2. 2. The laminated film according to claim 1, wherein, when the 50% stretch molding-reheating cycle test at Tn+20°C is repeated five times, the dimensional fixation rate after stretching in the fifth test is 90% or more, and the dimensional recovery rate after reheating in the fifth test relative to the initial dimension before the cycle test is 80% or more.

3. 3. The laminated film according to claim 1, wherein the thermoplastic resin A is crystalline.

4. 3. The laminated film according to claim 1, wherein the thermoplastic resin B is amorphous and the glass transition temperature of the B layer is Tn.

5. 3. The laminated film according to claim 1, wherein in the strain-stress curve in the tensile test at Tn+20° C., an inflection point appears for the first time at a strain of 50% or more when differential analysis is performed.

6. 3. The laminated film according to claim 1 or 2, wherein, when the storage modulus of layer A at temperature T (° C.) is GA(T) (GPa) and the storage modulus of layer B is GB(T) (GPa), 1.2GA(Tn-10)<GB(Tn-10) and GA(Tn+10)≧1.2GB(Tn+10) are satisfied.

7. The laminated film according to claim 1 or 2, wherein the Tn and Tm satisfy Tm-Tn≧30° C.

8. 3. The laminate film according to claim 1 or 2, wherein when dynamic viscoelasticity measurement is performed at a frequency of 10 Hz in a temperature range from -80°C to the melting point Tm, there are two or more loss tangent peaks, and the relationship between the loss tangent peak tanδ1 occurring at the lowest temperature (temperature T1 (°C)) and the loss tangent peak tanδ2 occurring at the highest temperature (temperature T2 (°C)) is tanδ2 / tanδ1≧1.

0.

9. 3. The laminated film according to claim 1, wherein the main component of the thermoplastic resin A is any one of polystyrene, polyester, polyurethane, and polyamide.

10. A sensor comprising the laminate film according to claim 1 or 2 and a stretchable conductive layer laminated thereon.

11. The sensor according to claim 10, which is used with its shape and function changed in a temperature range of 20 to 100°C.

12. 3. A tape comprising the laminate film according to claim 1 or 2 and an acrylic or silicone adhesive layer provided on at least one surface of the laminate film.

13. Water vapor permeability is 300 (g.25μm / (m 2 The tape according to claim 12, which is used in a temperature range of 20 to 50° C. while changing its shape and function.

Citation Information

Patent Citations

  • JP04991742B

  • Polyester molding having capability of shape memory

    JP1992122712A

  • Elastomer laminate with microtextured skin layer

    JP1993501386A

  • Shape-memory vulcanized rubber molding

    JP1997309986A

  • Stretchable film

    JP2017133011A